Esophageal transit time in patients with chagasic megaesophagus: Lack of linear correlation between dysphagia and grade of dilatation. Issue 10 (March 2018) - Martins, Paula; Ferreira, Cid Sergio; Cunha-Melo, José Renan
Abstract : Abstract: The aim of this study was to determine the esophageal transit time in control individuals and in chagasic patients with or without megaesophagus. A total of 148 patients were allocated in 6 groups according to serological diagnostic of Chagas disease and the degree of esophageal dilatation: A, control healthy individuals (n = 34, 22.9%); B, indeterminate form (n = 23, 15.5%); C, megaesophagus I (n = 37, 25.0%); D, megaesophagus II (n = 19, 12.8%); E, megaesophagus III (n = 21, 14.2%); and F, megaesophagus IV (n = 14, 9.5%). After 8-hour fasting, patients were asked to swallow 75 mL of barium sulfate solution. x-Rays were obtained after 8, 30, 60, and 90 seconds, 5, 10, 30, 60, and 90 minutes, 2, 6, 12, 24 hours, and at every 12 hours until no more contrast was seen in the esophagus. This was the transit time. The transit time varied from 8 seconds to 36 hours (median = 90 seconds). A linear correlation was observed between transit time and megaesophagus grade: 8 seconds in groups A and B, 5 minutes in C, 30 minutes in D, 2 hours in E, and 9:15 hours in F. Dysphagia was not reported by 60 of 114 (52.6%) patients with positive serological tests for Chagas disease (37/91—40.7%—of patients with megaesophagus I–IV grades). The esophageal transit time increased with the grade of megaesophagus. The esophageal transit time has a direct correlation with the grade of megaesophagus; dysphagia complaint correlates with the grade of megaesophagus. However, many patients with megaesophagus do not report dysphagia.